Slang Typologies and Subtitling Strategies in Spenser Confidential Movie - Muhammad Hajar Ibrahim; Ika Kartika Amilia (English Department - University of Sultan Ageng Tirtayasa, 2023)
This research analyzed the slang expressions used in the Indonesian subtitle of the 2020 movie, Spenser Confidential with the Indonesian subtitle from Netflix. This research sought out the type of slangs and the strategies used to translate the slangs into Indonesian. The research method used for this research is the qualitative method. This research uses type of slangs by Mattiello and subtitling strategies by Cintas and Remael. The type of slangs found within the movie are compounding, suffixation, conversion, acronym and initialisms, clipping, and word manufacture and fanciful formations, while the strategies used are simplifying verbal periphrases, using shorter near-synonym, changing word classes, changing negations or questions into affirmative sentences or assertions and indirect questions into direct questions, turning long and/or compound sentences into simple sentences, and omission. The subtitling strategies were used to eliminate parts of the messages that are deemed unimportant to the movie and reduce the amount of text displayed on the screen. Therefore, concepts were possible to be delivered more efficiently. In addition, cultural constraints may also be the reason as to why slangs were often omitted.